Single-cell sequencing reveals dysregulated cell type perturbations and critical mediator communication remodelling in colorectal cancer - Xu, Chengyuan; Zhang, Siqi; Zhang, Zhouyu; Zhang, Luoqiu; Sun, Bin; Yu, Zicheng; Liu, Hailong (Frontiers in Immunology, 2025)
BackgroundThe heterogeneity of colorectal cancer (CRC) and its complex immune microenvironment pose significant challenges for treatment. Understanding the cellular composition and dynamic changes is essential for uncovering mechanisms of tumour progression.MethodsTo investigate the cellular heterogeneity and immune microenvironment of CRC, identifying critical subpopulations, functional pathways, and prognostic biomarkers, single-cell transcriptomic data from 41 CRC samples across four datasets were integrated. Bioinformatic analyses identified cellular subpopulations, cell communication networks, and prognostic biomarkers. The expression patterns, clinical significance and biological function of TUBB were validated in vitro.ResultsA distinct epithelial subpopulation with proliferative and invasive features was identified, promoting tumour progression by resisting apoptosis and remodelling the extracellular matrix. ActMono, a terminal state of myeloid cells, was enriched in tumours and linked to disease progression. Cell communication analysis highlighted galectin signalling in immune regulation. A prognostic model (CRS) based on secretory immune cell-related genes identified TUBB as a key molecule influencing the cell cycle and extracellular matrix remodelling, with its expression patterns, clinical significance and biological effects validated in vitro.ConclusionThis study reveals critical subpopulations, signalling pathways, and biomarkers in CRC, providing insights into tumour progression and potential therapeutic strategies.